PSIX-40 Exogenous carbohydrases improve carcass characteristics of Nellore beef cattle grazed in tropical conditions. (5th December 2019) - Vasconcellos, Guilherme S; Perdigão, Alexandre; Acedo, Tiago S; Carvalho, Victor V; Tamassia, Luis Fernando
Abstract: The objective was to evaluate the effects of feeding levels of an exogenous carbohydrases blend on performance and carcass characteristics of grazing Nellore beef cattle. A total of 168 bulls were distributed to twenty Brachiaria brizantha cv. Xaraés paddocks (8 or 10 animals/paddock) in a randomized complete block design, with five replicates (paddocks) per treatment. Bulls were assigned according initial BW (IBW; 369.07±21.13 kg) to receive treatments for 231 days: 1) Control (basal mineral-protein-energetic supplement, no enzyme; PES), Carb1 (PES + 0.83 g of xylanase, RONOZYME® WX; and 3.09 g of beta-glucanase, RONOZYME® VP, both offered/kg PES), Carb2 (PES + 1.65 g of xylanase and 6.18 g of beta-glucanase/kg PES) and Carb3 (PES + 3.30 g of xylanase and 12.38 g of beta-glucanase/kg PES). Evaluated parameters were final BW (FBW), average daily gain (ADG), supplement intake, hot carcass weight (HCW) and dressing %. IBW and FBW were measured after a 12-hour fastening period. Treatments were offered daily in covered group feeders located in each paddock. Animals had free access to supplements and water. Supplements and enzymes were provided by DSM Nutritional Products. Data were analyzed using MIXED procedure of SAS® 9.3, being each paddock the experimental unit. Orthogonal contrasts were used to detect linear and quadratic effects on enzyme levels, with values P ≤ 0.05 considered significant. No linear or quadratic effects (P > 0.05) were observed on supplement intake (2.11 kg/animal/d), FBW (492.03 kg) and ADG (0.532 kg/day). However, a quadratic effect was observed for HCW and dressing %, with animals fed Carb1 presenting 5.69 kg heavier carcass (272.67 vs. 266.98; P = 0.039) and 1.4 p.p. higher dressing % (55.3% vs. 53.9%, P < 0.001) compared with control group. In conclusion, to use carbohydrases enzyme blend improves carcass characteristics and is an interesting technology for Nellore beef cattle grazed in tropical conditions.